An investigation into the cold start performance of automotive diesel engines - Burrows, John Antony (1998)
The cold start performance of automotive diesel engines is currently poor when compared to similar gasoline units. This thesis describes an experimental and theoretical investigation into the factors limiting diesel cold start behaviour. Studies have been carried out on IDI and DI designs of engine. Start behaviour has been characterised in terms of times taken to complete various stages of startup, engine speed variations and processes which affect these. Combustion and friction behaviour have been investigated in detail.